Analisis Perceived Value, Service Quality dan Promotion Terhadap Customer Loyalty melalui Customer Satisfaction sebagai Variabel Mediasi: Studi pada Pengguna Netflix Aplikasi Streaming Film - Assasudin Assyafi; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2025)
This study was conducted with the aim of analyzing the factors that influence customer loyalty among users of the Netflix streaming platform, with customer satisfaction as the intervening variable. As competition in the online streaming service industry becomes increasingly intense, a decrease in Netflix user traffic by 970,000 users in 2022 indicates a potential issue with customer loyalty. This research aims to examine the effect of perceived value, service quality, and promotion on customer loyalty, mediated by customer satisfaction. The research data was collected from a total of 150 respondents who are Netflix users in Semarang City through a questionnaire consisting of closed-ended questions using a 1–10 scale, which was distributed online. The analysis was conducted using the Structural Equation Model (SEM) method with AMOS 24 software. The results of this study indicate that perceived value, service quality, and promotion have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty